High-mechanical-strength and high-viscosity hemostatic and anti-adhesion combined material, preparation method and application
By using the combined crosslinking material of modified alginate and gelatin combined with crosslinking components, the problem of insufficient mechanical strength and viscosity of existing hemostasis and anti-adhesion materials is solved, and efficient and stable postoperative hemostasis and anti-adhesion effects are achieved.
Patent Information
- Application Number
- CN202411581401.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-07
- Publication Date
- 2025-03-14
AI Technical Summary
The existing hemostasis and anti-adhesion materials have problems such as insufficient mechanical strength and viscosity, large dosage, and unstable effect during postoperative use, and cannot fully meet clinical needs.
A combination of crosslinking materials, including alginate and gelatin as gelatin, is used to increase the crosslinking degree through modification reactions and combine with the crosslinking components in the spray to form an anti-adhesion implantable material with high mechanical strength and high viscosity.
It achieves high mechanical strength and high viscosity, prevents postoperative adhesion, displacement and bacterial infection, and is simple and fast in preparation, suitable for portable and convenient use multi-functional anti-adhesion products.
Smart Images

Figure CN119607252A_ABST
Abstract
Description
Technical Field
[0001] The present disclosure relates to the technical field of biomedical materials, and in particular to a hemostatic and anti-adhesion combined use material with high mechanical strength and high viscosity, a preparation method and application thereof. Background Art
[0002] Postoperative adhesion is the symptom with the highest incidence rate among postoperative complications. It can cause pain to the patient's recovery at the mildest level, and serious diseases such as ischemia and intestinal obstruction at the worst level. It is a type of complication that needs to be solved urgently. Most of the existing materials have single functionality, require large dosage, and unstable product effects, which have caused serious psychological and economic burdens on patients. The mainstream anti-adhesion materials at home and abroad are mainly divided into three dosage forms, namely patches such as polylactic acid anti-adhesion film; hydrogels such as sodium hyaluronate gel and sprays such as polylactic acid anti-adhesion spray. Among them, patch products, if they do not have adhesion properties, will cause secondary damage to the wound when used and have poor adaptability to the wound; if they are sticky, the adhesive will have a certain inhibitory effect on the recovery of the wound; hydrogel products have large dosage and unstable anti-adhesion effect, low mechanical strength and viscosity; the film-forming speed of spray products needs to be further improved. For the actual clinical needs, the products currently on the market cannot fully meet them. Therefore, it is very necessary to develop a multifunctional degradable hemostatic material that has both hemostasis and anti-adhesion, can stably adhere to the wound surface, is antibacterial, and promotes repair.
[0003] Therefore, it is very necessary to develop a repair implant material that has high mechanical strength, high viscosity, anti-adhesion, and the ability to prevent displacement. Summary of the invention
[0004] The purpose of the present disclosure is to provide an anti-adhesion implant material with high mechanical strength and high viscosity to solve the postoperative risks caused by postoperative adhesion, displacement or bacterial contamination of the implant, and to make up for the shortcomings of existing anti-adhesion implant products. At the same time, another purpose of the present invention is to provide a method for simply and quickly preparing the above-mentioned implant material, and to use the above-mentioned implant material to prepare a portable, easy-to-use and multifunctional anti-adhesion product.
[0005] In order to achieve the above objectives, the present disclosure provides the following technical solutions:
[0006] In a first aspect, the present disclosure provides a combination of cross-linked materials, including a gel and a spray; the gel includes two gel components, alginate and gelatin, at least one of the alginate and gelatin has undergone a modification reaction for the purpose of increasing the degree of cross-linking, or at least one of the alginate and gelatin contains a modification group that increases the degree of cross-linking; the spray contains one cross-linking component, two cross-linking components, or a combination of two or more cross-linking components that can undergo a cross-linking reaction with alginate and / or gelatin.
[0007] In some optional embodiments, both the alginate and gelatin in the gel are modified, and self-crosslinking occurs between the two gel components and / or between themselves; preferably, the self-crosslinking is photo-crosslinking.
[0008] In some optional embodiments, the alginate is subjected to an oxidative modification reaction to carry a hydroxyl group, a carboxyl group, a phenolic group, an aldehyde group or any combination thereof; the gelatin contains a modification group selected from an acetyl group or a part, a phenolic group or a part, a thiol group or a part, a norbornene group or a part, a tetrazine group or a part, an azido group or a part, a furan group or a part, or any combination thereof;
[0009] Preferably, the modifying group is methacryloyl and / or acryloyl.
[0010] In some optional embodiments, the mass ratio of alginate to gelatin is 1:(0.1-30), preferably 1:(0.5-30), and further preferably 1:(1-10); the spray contains a first cross-linking component and a second cross-linking component cross-linked with alginate and gelatin, respectively, and the mass concentration ratio of the first cross-linking component to the second cross-linking component is (2-50):1, preferably (10-50):1, and further preferably (15-30):1.
[0011] In some optional embodiments, the molecular weight ratio of the first cross-linking component to the second cross-linking component is at least 1:(20-100). In some optional embodiments, the monomolecular charge difference between the first cross-linking component and the second cross-linking component is at least 1; preferably, the monomolecular charge difference is 2.
[0012] In some alternative embodiments, the cross-linking component includes calcium ions and tannic acid.
[0013] In some optional embodiments, the gel and / or spray further contains functional molecules, including but not limited to antimicrobial agents, coagulants or viscosity enhancers; preferably, the antimicrobial agent is selected from at least one of silver ions, antibiotics or antimicrobial peptides; preferably, the coagulant is selected from at least one of tranexamic acid, carbon nanofibers, fibrin or thrombin.
[0014] In a second aspect, the present disclosure provides a method for preparing the cross-linked material combination described in the first aspect of the present disclosure, including a relatively independent method for preparing a gel and a method for preparing a spray; the method for preparing the gel includes, after alginate and gelatin are modified, aqueous solutions are prepared separately, the concentration of modified alginate in the modified alginate aqueous solution is 1% to 30% (w / v), and the concentration of modified gelatin in the modified gelatin aqueous solution is 5.0% to 30.0% (w / v), and then the two aqueous solutions are mixed in a volume ratio of 1:1 to 5:1; the method for preparing the spray includes, separately preparing aqueous solutions of different cross-linked components, and then mixing them.
[0015] In some optional embodiments, the modified alginate aqueous solution and / or the modified gelatin aqueous solution contains a photocrosslinking initiator; preferably, the photocrosslinking initiator is selected from one or more of phenyl-2,4,6-trimethylbenzoyl phosphinate lithium, benzophenone, 2-hydroxy-4'-(2-hydroxyethoxy)-2-methylpropiophenone, 2-hydroxy-2-methyl-1-phenylpropiophenone, 1-hydroxy-cyclohexylacetone, hydroxybenzophenone, benzoyldiphenylphosphine, benzophenone, and 2,2'-azobis(2-methylpropionitrile).
[0016] In some optional embodiments, the cross-linking component includes calcium chloride and tannic acid. The preparation method of the spray includes dissolving calcium chloride in water to prepare a 1.0% to 5% (w / v) calcium chloride solution, dissolving tannic acid in water to prepare a 0.1 g / ml solution, and mixing the calcium chloride solution to the tannic acid solution in a volume ratio of 1:1 to 1:5.
[0017] In some optional embodiments, the method for preparing the gel and / or the method for preparing the spray further comprises the step of adding functional molecules.
[0018] In a third aspect, the present disclosure provides the use of the cross-linked material combination described in the first aspect, or the cross-linked material combination prepared by the preparation method described in the second aspect, in the preparation of hemostatic, antibacterial or anti-adhesion products.
[0019] In a fourth aspect, the present disclosure provides an implant dressing, comprising the cross-linked material combination described in the first aspect of the present disclosure, or the cross-linked material combination prepared by the preparation method described in the second aspect of the present disclosure.
[0020] In a fifth aspect, the present disclosure provides a portable tool box, comprising the implant material described in the first aspect, or a cross-linked material combination prepared by the preparation method described in the second aspect.
[0021] In a sixth aspect, the present disclosure provides a method for postoperative hemostasis, adhesion prevention or implant displacement prevention in vivo, comprising applying the implant material described in the first aspect, or the implant material prepared by the preparation method described in the second aspect, to a postoperative wound site.
[0022] In the seventh aspect, the present disclosure provides a hemostatic device, comprising a pressure device, a dried implant material filled in the pressure device, and a spray, wherein the implant material comprises the gel in the cross-linked material combination described in any one of the aforementioned embodiments or the gel in the cross-linked material combination prepared by the preparation method described in any one of the aforementioned embodiments; the spray comprises the spray in the cross-linked material combination described in any one of the aforementioned embodiments or the spray in the cross-linked material combination prepared by the preparation method described in any one of the aforementioned embodiments; preferably, the pressure device comprises a syringe.
[0023] In an eighth aspect, the present disclosure provides a hemostasis platform or system, comprising the hemostasis device described in the seventh aspect.
[0024] In the anti-adhesion material used in combination with the gel and spray provided by the present disclosure, both alginate and gelatin introduce adhesive groups for the purpose of increasing the degree of cross-linking, and in some specific embodiments, the cohesion is further increased by photo-cross-linking, and at the same time, the modified groups of alginate react with the amino groups in the tissue of the repair site to further increase the viscosity. The modified gelatin can self-cross-link, and a Schiff base reaction occurs between the modified gelatin and sodium alginate, and at the same time, the photo-cross-linking further increases the mechanical strength. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] In order to more clearly illustrate the specific embodiments of the present disclosure or the technical solutions in the prior art, the drawings required for use in the specific embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some embodiments of the present disclosure. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative work.
[0026] Figure 1 GMOSB in Example 1 S Schematic diagram of the hemostasis process;
[0027] Figure 2 The synthetic characterization results of GMOS in Example 1;
[0028] Figure 3 This is a diagram showing the gelling experiment results in Example 1;
[0029] Figure 4 The injectability performance analysis results in Example 1;
[0030] Figure 5The rheological properties test results in Example 1;
[0031] Figure 6 The results of the self-healing performance test in Example 1 are as follows;
[0032] Figure 7 The swelling rate test results in Example 1;
[0033] Figure 8 The adhesion strength test results in Example 1;
[0034] Fig. 9 The results of the test on the adhesion ability of GMOS to major organs in Example 1;
[0035] Fig.10 The following are the test results of the adhesion ability of GMOS to pig skin in Example 1;
[0036] Fig.11 GMOSB in Example 1 S Burst pressure test results;
[0037] Fig.12 For example, L929 in the orifice plate and GMOSB S Comparison of 24h growth;
[0038] Fig.13 The anti-adhesion performance evaluation results in Example 1;
[0039] Fig.14 The results of liver hemostasis performance evaluation in Example 1;
[0040] Fig.15 The metabolic safety assessment results in Example 1;
[0041] Fig.16 The results of related performance evaluation in the rat femoral artery injury model in Example 1;
[0042] Fig.17 These are the results of evaluating the hemostatic effect in the rat heart injury model in Example 1. DETAILED DESCRIPTION
[0043] In order to make the purpose, technical solutions and advantages of the embodiments of the present disclosure clearer, the technical solutions in the embodiments of the present disclosure will be clearly and completely described below in conjunction with the drawings in the embodiments of the present disclosure. Obviously, the described embodiments are part of the embodiments of the present disclosure, rather than all of the embodiments.
[0044] (I) Definitions or terms
[0045] The following abbreviations are used for the relevant definitions or terms involved in this disclosure. Unless otherwise defined, all scientific and technological terms used herein have the meanings commonly understood by those of ordinary skill in the art. The following terms are provided below.
[0046] As used herein, the terms "a" and "an" and "the" and similar referents refer to both the singular and the plural, unless otherwise indicated herein or clearly contradicted by context.
[0047] As used herein, the conjunction term "and / or" between a variety of described elements is understood to include both single options and combined options. For example, when two elements are connected by "and / or", the first option refers to the applicability of the first element without the second element. The second option refers to the applicability of the second element without the first element. The third option refers to the applicability of the first and second elements together. Any of these options is understood to fall within the meaning, thus satisfying the requirements of the term "and / or" used herein. The concurrent applicability of multiple options is also understood to be the meaning of the term, thus satisfying the requirements of the term "and / or".
[0048] As used herein, the terms "adhesion" and "adhesion" are used interchangeably and refer to the phenomenon that tissue membranes or parts of different tissue origins or components in the body adhere to each other after physical contact, and require a certain external force to separate.
[0049] As used herein, the term "antimicrobial agent" refers to a substance that kills or inhibits the growth of microorganisms such as bacteria, fungi, archaea, or protozoa. Antimicrobial agents either kill microorganisms or prevent the growth of microorganisms. In one or more embodiments, the antimicrobial agent includes, but is not limited to, at least one of silver ions, antibiotics, or antimicrobial peptides.
[0050] As used herein, the term "coagulant" refers to a substance that can accelerate the formation of a cross-linked complex obtained by the reaction of the framework components. Such substances are well known to those skilled in the art and may include, but are not limited to, tranexamic acid, carbon nanofibers, fibrin, and thrombin.
[0051] (II) Detailed technical solution
[0052] In a first aspect, the present disclosure provides a combination of cross-linked materials, including a gel and a spray; the gel includes two gel components, alginate and gelatin, at least one of the alginate and gelatin has undergone a modification reaction for the purpose of increasing the degree of cross-linking, or at least one of the alginate and gelatin contains a modification group that increases the degree of cross-linking; the spray contains one cross-linking component, two cross-linking components, or a combination of two or more cross-linking components that can undergo a cross-linking reaction with alginate and / or gelatin.
[0053] In some optional embodiments, both the alginate and gelatin in the gel are modified, and self-crosslinking occurs between the two gel components and / or between themselves; preferably, the self-crosslinking is photo-crosslinking.
[0054] In some optional embodiments, the alginate carries a hydroxyl group, a carboxyl group, a phenolic group, an aldehyde group or any combination thereof after an oxidative modification reaction; the gelatin contains a modification group selected from an acetyl group or part, a phenolic group or part, a thiol group or part, a norbornene group or part, a tetrazine group or part, an azide group or part, a furan group or part, or any combination thereof; preferably, the modification group is a methacryloyl group and / or an acryloyl group.
[0055] In some optional embodiments, the mass ratio of alginate to gelatin is (0.1-30), preferably 1:(0.5-30), and further preferably 1:(1-10); the spray contains a first cross-linking component and a second cross-linking component cross-linked with alginate and gelatin, respectively, and the mass concentration ratio of the first cross-linking component to the second cross-linking component is (2-50):1, preferably (10-50):1, and further preferably (15-30):1.
[0056] In some optional embodiments, the molecular weight ratio of the first cross-linking component to the second cross-linking component is at least 1:(20-100).
[0057] In some optional embodiments, the monomolecular charge difference between the first cross-linking component and the second cross-linking component is at least 1; preferably, the monomolecular charge difference is 2.
[0058] In some alternative embodiments, the cross-linking component includes calcium ions and tannic acid.
[0059] In some optional embodiments, the gel and / or spray further contains functional molecules, including but not limited to antimicrobial agents, coagulants or viscosity enhancers; preferably, the antimicrobial agent is selected from at least one of silver ions, antibiotics or antimicrobial peptides; preferably, the coagulant is selected from at least one of tranexamic acid, carbon nanofibers, fibrin or thrombin.
[0060] In a second aspect, the present disclosure provides a method for preparing the cross-linked material combination described in the first aspect of the present disclosure, including a relatively independent method for preparing a gel and a method for preparing a spray; the method for preparing the gel includes, after alginate and gelatin are modified, aqueous solutions are prepared separately, the concentration of modified alginate in the modified alginate aqueous solution is 1% to 30% (w / v), and the concentration of modified gelatin in the modified gelatin aqueous solution is 5.0% to 30.0% (w / v), and then the two aqueous solutions are mixed in a volume ratio of 1:1 to 5:1; the method for preparing the spray includes, separately preparing aqueous solutions of different cross-linked components, and then mixing them.
[0061] In some optional embodiments, the modified alginate aqueous solution and / or the modified gelatin aqueous solution contains a photocrosslinking initiator; preferably, the photocrosslinking initiator is selected from one or more of phenyl-2,4,6-trimethylbenzoyl phosphinate lithium, benzophenone, 2-hydroxy-4'-(2-hydroxyethoxy)-2-methylpropiophenone, 2-hydroxy-2-methyl-1-phenylpropiophenone, 1-hydroxy-cyclohexylacetone, hydroxybenzophenone, benzoyldiphenylphosphine, benzophenone, and 2,2'-azobis(2-methylpropionitrile).
[0062] In some optional embodiments, the cross-linking component includes calcium chloride and tannic acid. The preparation method of the spray includes dissolving calcium chloride in water to prepare a 1.0% to 5% (w / v) calcium chloride solution, dissolving tannic acid in water to prepare a 0.1 g / ml solution, and mixing the calcium chloride solution to the tannic acid solution in a volume ratio of 1:1 to 1:5.
[0063] In some optional embodiments, the method for preparing the gel and / or the method for preparing the spray further comprises the step of adding functional molecules.
[0064] In a third aspect, the present disclosure provides the use of the cross-linked material combination described in the first aspect, or the cross-linked material combination prepared by the preparation method described in the second aspect, in the preparation of hemostatic, antibacterial or anti-adhesion products.
[0065] In a fourth aspect, the present disclosure provides an implant dressing, comprising the cross-linked material combination described in the first aspect of the present disclosure, or the cross-linked material combination prepared by the preparation method described in the second aspect of the present disclosure.
[0066] In a fifth aspect, the present disclosure provides a portable tool box, comprising the implant material described in the first aspect, or a cross-linked material combination prepared by the preparation method described in the second aspect.
[0067] In a sixth aspect, the present disclosure provides a method for postoperative hemostasis, adhesion prevention or implant displacement prevention in vivo, comprising applying the implant material described in the first aspect, or the implant material prepared by the preparation method described in the second aspect, to a postoperative wound site.
[0068] In the seventh aspect, the present disclosure provides a hemostatic device, comprising a pressure device, a dried implant material filled in the pressure device, and a spray, wherein the implant material comprises the gel in the cross-linked material combination described in any one of the aforementioned embodiments or the gel in the cross-linked material combination prepared by the preparation method described in any one of the aforementioned embodiments; the spray comprises the spray in the cross-linked material combination described in any one of the aforementioned embodiments or the spray in the cross-linked material combination prepared by the preparation method described in any one of the aforementioned embodiments; preferably, the pressure device comprises a syringe.
[0069] In an eighth aspect, the present disclosure provides a hemostasis platform or system, comprising the hemostasis device described in the seventh aspect.
[0070] (II) Detailed Implementation Plan
[0071] Some embodiments of the present disclosure are described in detail below in conjunction with the accompanying drawings. In the absence of conflict, the following embodiments and the features in the embodiments can be combined with each other. The following examples are used to further illustrate the present invention, but should not be construed as limiting the present invention. Any other changes, modifications, substitutions, combinations, and simplifications made without departing from the spirit and principle of the present invention should all be equivalent replacement methods and are included in the protection scope of the present invention. If not specifically stated, the technical means used in the embodiments are conventional means well known to those skilled in the art.
[0072] Example 1: Preparation of anti-adhesion gel spray combination
[0073] 1.1. Preparation of sol
[0074] A 0.25% phenyl-2,4,6-trimethylbenzoyl phosphinate lithium solution is prepared as a solvent for subsequent gelation. The methacrylic acylated gelatin trimethylbenzoyl phosphinate lithium solution and the oxidized sodium alginate trimethylbenzoyl phosphinate lithium solution are mixed in a ratio of 1:1 to 1:5 to prepare a precursor sol. When used, the sol is injected into the wound site using a syringe, and an adhesive hydrogel can be formed in situ after irradiation with 405nm ultraviolet excitation light for 30s to 60s.
[0075] 1.2. Preparation of the spray part
[0076] Dissolve anhydrous calcium chloride in deionized water to prepare a calcium chloride solution, dissolve tannic acid in ultrapure water to prepare a 0.1 g / ml solution, mix the two evenly, put them into a spray bottle for sterile storage. When in use, spray evenly on the surface of the hydrogel to form a smooth film-like structure.
[0077] After multiple batches of experiments, the specific amounts of each parameter in the above preparation steps were adjusted, and then the viscosity and mechanical strength of the prepared anti-sticking composite material were tested according to the following viscosity and mechanical strength test methods.
[0078] 1.3. Viscosity test
[0079] The tissue adhesion ability of the repair material was evaluated by the fresh pig skin adhesion tensile test. Take a fresh pig skin with a length of 3 cm and a width of 1 cm, and use a syringe to inject the sol part onto the pig skin to form a 1cm×1cm sol layer. After irradiation with 405nm ultraviolet excitation light for 30s to 60s, an adhesive hydrogel can be formed in situ. Another pig skin is overlapped on the surface of the hydrogel so that the two pig skins are in contact without giving additional pressure. Then the spray part is sprayed on the surface of the adhesive hydrogel through the gap of the pig skin to enhance its cross-linking strength. Finally, the adhesion strength between the material and the fresh pig skin is measured by an electromechanical universal testing machine (MTS).
[0080] 1.4. Mechanical strength test
[0081] The repair material provided in this embodiment was subjected to a compression test at room temperature using an Instron material testing system (Instron 3345). The hydrogel material was prepared according to step 1.1, and then freeze-dried and trimmed to obtain a cylindrical shape with a diameter of 8 mm and a height of 12 mm. The freeze-dried repair material was then expanded in pure water, and then a smooth membrane structure was prepared on the surface of the repair material according to step 1.2. The material was then subjected to a compression test to examine the maximum compression strain at a strain rate of 100 μm / s.
[0082] The specific parameters in the above steps, as well as the shape memory ability and anti-adhesion ability test results in different experimental batches are shown in Tables 1 and 2:
[0083] Table 1. Comparison table of specific parameters of different experimental batches
[0084]
[0085] Table 2. Specific parameter values for different experimental batches
[0086] Experimental batch A B C D E 1 10% 20% 1:1 4% 1:1 2 20% 20% 1:1 4% 1:1 3 30% 20% 1:1 4% 1:1
[0087] It can be seen from the above that according to the preparation method provided in this embodiment, when the concentration of methacrylic acylated gelatin solution is 5.0% to 30.0% (w / v), the concentration of oxidized sodium alginate solution is 1% to 30% (w / v), the volume ratio of gelatin solution to sodium alginate solution is 1:1 to 1:5, the concentration of calcium chloride aqueous solution is 1.0% to 5% (w / v), and the volume ratio of calcium chloride solution to tannic acid solution is 1:1 to 1:5, the prepared cross-linked material has a compressive strain energy of more than 75%, a viscosity of more than 45 kPa, has high mechanical strength and high viscosity, and is suitable for repairing wound sites with high implant stress.
[0088] 1.5. Synthesis and characterization of gel repair material (GMOS)
[0089] First pass 1 H NMR characterization of methacryloyl acylated gelatin (GELMA) and oxidized sodium alginate (OSA) showed that Figure 2 As shown in Figure A, it can be seen that compared with gelatin (GEL), GELMA has characteristic resonances of methacrylate groups at δ = 5.3 ppm and δ = 5.6 ppm. In Figure B, OSAFT-IR at 1738 cm -1 A new characteristic peak appears at 1640 cm-1, which corresponds to the aldehyde group (-CHO). The peak is not obvious because it is caused by the hemiacetal of the free aldehyde group. -1 The characteristic absorption peak of imine stretching vibration (-C=N-) appears at Figure 2 ), indicating the formation of a dynamic Schiff base bond.
[0090] 1.6. Gelation time analysis
[0091] The gelation process of GMOS mainly includes Schiff base reaction and ultraviolet light-excited imine cross-linking reaction. When GELMA and OSA are evenly mixed, in-situ gelation can be achieved by Schiff base reaction, but the gelation speed is slow. Figure 3 As shown, GMOS can form a hydrogel when OSA is mixed with GELMA.
[0092] At 37°C, the gelation time of each group was detected by the inversion method. As shown in Table 3, after UV irradiation, the time required for gelation was significantly reduced. The 10% GELMA + 10% OSA group and the 10% GELMA + 15% OSA group were able to gel within 30 seconds of irradiation. The gelation speed of the 10% GELMA + 5% OSA group was relatively slow, but it was also guaranteed to gel within 50 seconds. After spraying, all three groups were able to quickly complete the gelation process within 5 seconds. The continuous reduction in gelation time also proves the positive effect of increasing cross-linking strength on the gelation speed. Rapid gelation can not only achieve wound closure in a short time, but also reduce the risk of inflammation to surrounding tissues caused by the flow of materials.
[0093] Table 3. Gelation time
[0094]
[0095]
[0096] 1.7. Injectability performance analysis
[0097] Considering that GELMA and OSA can form hydrogel after contact, which affects the smoothness of injection, GMOS is injected with two syringes. Figure 4 As shown: Use a double syringe with a needle equipped with GMOS to write "TJU" on the glass plate, carefully record the experience during the injection process and observe the uniformity of the injected font. It can be seen that the fonts injected by the 10% GELMA+5% OSA group and the 10% GELMA+10% OSA group are uniform and the injection process is very smooth; while the 10% GELMA+15% OSA group has obvious resistance during the injection process and the injected font is interrupted and the lines are uneven.
[0098] 1.8. Rheological behavior and self-healing properties
[0099] The stability of the gel and whether G' is improved need further verification. The stable gel state can ensure that GMOSB S According to the detection method described in the reference: Biomimetic hybrid hydrogel for hemostasis, adhesion prevention and promoting regeneration after partial liver resection (doi.org / 10.1016 / j.bioactmat.2021.10.001), GMOSB S The rheological behavior of Figure 5 As shown, for three groups of GMOSBS Rheological tests were performed on G' and G" at different cross-linking stages. The G' of all samples tested was higher than G", indicating that GMOS can achieve the transition from sol to gel without the assistance of other means and can maintain a hydrogel state at 37°C. In the same ratio group, G' can be improved with each additional cross-linking method (UV irradiation or use of B spray), which proves the effectiveness of the cross-linking method. With the increase of OSA content, G' also increases. This is because the increase in aldehyde groups increases the number of Schiff base reactions and improves the cross-linking strength of the material; the 15% OSA group has an uneven internal structure due to the excessively fast cross-linking speed, which affects the continued improvement of G'.
[0100] Furthermore, as a degradable biomaterial, stability and integrity during implantation in the body are very important. Material damage will not only affect the function of the material, but the broken material may also damage the surrounding tissues. When the patient exercises, the material may break or be damaged due to changes in body position. The self-healing properties of GMOS can solve this problem well. When the hydrogel is damaged, the amino group in GELMA and the aldehyde group in OSA can undergo a reversible Schiff base reaction under physiological conditions, helping GMOS to complete self-healing in a short time. Figure 6 As shown in the figure, both the 10% GELMA+5% OSA group and the 10% GELMA+10% OSA group were able to complete self-healing within 3 minutes. Due to the decrease in flowability as the concentration increased in the 10% GELMA+15% OSA group, local gelation occurred during double syringe injection, resulting in uneven sample thickness and cross-linking strength in this group. In order to form a complete columnar sample, the self-healing performance could not be investigated.
[0101] 1.9. Swelling behavior and mechanical strength analysis
[0102] Appropriate swelling can maintain the moist environment required for wound healing and absorb wound exudate at any time, but excessive swelling will squeeze the surrounding tissue and reduce the mechanical properties of the hydrogel. Figure 7 As shown, the three groups of GMOSB detected S The swelling rates are all below 80%, which can ensure the liquid absorption capacity while keeping the loss of mechanical properties and the impact on surrounding tissues within a controllable range. Studies have shown that the cross-linking strength has a significant effect on the swelling rate of the material, and an increase in the cross-linking strength helps to reduce the degree of swelling. The increase in OSA concentration leads to an increase in the aldehyde content, which increases the intensity of the Schiff base reaction in the system, thereby reducing the overall swelling of the material.
[0103] High cross-linking not only helps to reduce the swelling rate, but also increases the mechanical properties of the hydrogel system. As shown in Table 4, compared with 30% GEL+2% SA+BS Young's modulus of hydrogel, GMOSB S The Young's modulus of the system is significantly improved. This is due to the introduction of the photocrosslinking system and Schiff base reaction, 10% GELMA + 10% OSA + B S The mechanical properties are the best, reaching 2451.21kPa, ensuring that the material will not break when subjected to external forces during normal human movement. 10% GELMA + 15% OSA + B S The mechanical properties of the group did not further improve with the increase of OSA concentration due to the uneven gelation rate.
[0104] Table 4. GMOSB in each group S Young's modulus
[0105]
[0106]
[0107] 1.10. Analysis of tissue adhesion properties and bursting pressure
[0108] The tissue adhesion strength of GMOS is better than that of AMOS due to the Schiff base reaction between OSA and tissue amino groups, the imine cross-linking induced by UV irradiation, and the hydrogen bond between tissue and material. G According to the reference Biomimetic hybrid hydrogel for hemostasis, adhesion prevention and promoting regeneration after partial liver resection
[0109] The adhesion strength was tested using the detection method described in (doi.org / 10.1016 / j.bioactmat.2021.10.001), and the results were as follows Figure 8 As shown in the figure, the adhesion strength of the 10% GELMA + 10% OSA group is higher than that of the 10% GELMA + 5% OSA group. This is due to the combined effect of the increased aldehyde concentration in GMOS, which increases the binding strength with tissue amino groups, and the increased cross-linking strength of the hydrogel on the cohesive force. However, when the OSA concentration is too high, the molecular motion is affected, and the cross-linking speed is too fast, resulting in uneven gelation in the 10% GELMA + 15% OSA group, which affects the cohesive force of the hydrogel, and thus the adhesion strength decreases. Fig. 9 It can be seen that GMOS (10% GELMA+
[0110] 10% OSA group, the same below) can adhere the heart, liver, spleen, and lung to the glass plate, proving that it can adhere to a variety of important organs.
[0111] Apply the dyed GMOS on the treated pigskin, then twist, fold and stretch the pigskin to observe the GMOS condition. Fig.10 As shown, GMOS always adheres tightly to the pig skin during a series of movements, and there is no separation between the edge and the pig skin. The hydrogel remains intact throughout the entire movement without obvious damage, proving that GMOS can stably adhere to the surface of skin tissue within the normal range of movement.
[0112] In order to complete the hemostatic treatment of vascular bleeding and resist the destructive effect of blood pressure on the material, it is far from enough to rely solely on the tissue adhesion effect, and it should also have a burst pressure exceeding normal blood pressure. To this end, according to the method described in the reference: A strongly adhesive hemostatic hydrogel for the repair of arterial and heart bleeds (https: / / doi.org / 10.1038 / s41467-019-10004-7), the main blood vessels of pigs were used as a model to simulate vascular bleeding in vivo, and GMOSB was detected. S The bursting pressure of a series of materials, the experimental results are as follows Fig.11 The 10% GELMA+10% OSA group with uniform gelation and reasonable proportion had the most ideal burst pressure, reaching 130.01 mmHg, which exceeded the normal systolic blood pressure of 120.00 mmHg in the human body, and had the potential to be used in the hemostasis treatment of vascular injury.
[0113] 1.11. Evaluation of anti-adhesion performance
[0114] The adhesion and proliferation of fibroblasts affect the speed and degree of adhesion formation. In the initial stage of adhesion formation, fibroblasts need to attach to the surface of the wound and the adhesion organ as the basis of the adhesion structure. S Co-culture, and evaluate the anti-adhesion effect by observing the cell growth status and adhesion. Fig.12 As shown, L929 cells grown in the well plate showed normal cell morphology, with clear and stretched borders and normal proliferation. S The L929 cells on the hydrogel surface showed a rounded contraction state, without adhesion and proliferation, and the number of surface adherent cells was significantly lower than that of the normal group. S It has a significant inhibitory effect on the adhesion of fibroblasts.
[0115] The rat cecal injury model with high recognition was used to investigate GMOSB S The anti-adhesion effect was evaluated in vivo. Fig.13As shown in the figure, 14 days after successful modeling, the rats in the model group that did not use any anti-adhesion materials had severe adhesions between the abdominal wall and the cecum, and there was a large area of adhesion between the injured cecum, the surrounding mesentery and the abdominal wall that could not be separated. The commercial hydrogel group used as the positive control lacked the ability to stably cover the wound, and the anti-adhesion effect was unstable. Occasionally, there was adhesion with other mesentery or intestinal tracts, and the degree of adhesion varied, which may be related to the degree of flow caused by the rat movement on the commercial hydrogel. GMOSB S In the group, the material was still tightly adhered to the wound surface 14 days after the injury. There was no adhesion between the cecum and the surrounding tissues in most rats. Only one case of slight adhesion between the material and the mesentery occurred, which could be easily peeled off with a cotton swab. Analysis showed that the cause of this adhesion was that the GMOS was not completely covered when the spray was applied. In the H&E staining of the model group, obvious adhesion tissue and inflammatory cells were seen. In the Masson staining, there was obvious fibrous deposition in the adhesion area, proving that an adhesion structure had formed between the cecum and the abdominal wall. In the commercial hydrogel group, adhesion structures between the mesentery and the cecum were visible, but the adhesion area was reduced. GMOSB S The H&E and Masson staining of the group showed that the material was present on the surface of the cecum. Analysis showed that the gap between the cecum and the material was caused by the different degrees of contraction of the tissue and the material during dehydration. S Both commercial hydrogels effectively reduced the occurrence of adhesion. S It has a more stable anti-adhesion effect. S The anti-adhesion properties of SA depend on its physical barrier function, anti-fibroblast adhesion function and anti-inflammatory effect. Fig.13 (A) 14 days after surgery without treatment, commercial hydrogel treatment (surgical anti-adhesion solution (Cerbitol) Cycs Biotech Co., Ltd.) and GMOSB S (Experimental batch 1 in Example 1) The cecal adhesion of the treated rats, H&E and Masson staining. Mesentery: mesentery; AW: abdominal wall; Me: mesothelial layer. The dotted line in the figure indicates the remaining GMOSB S (B) Statistics of adhesion scores in each group.
[0116] 1.12. Evaluation of hemostatic performance and in vivo metabolic safety in the SD rat liver injury model
[0117] To investigate GMOSB S The in vivo hemostatic performance and metabolic safety of the drug were evaluated using a rat liver injury model. Fig.14 As shown, compared with the gauze control group, the commercial hydrogel group, GMOSB SThe bleeding time and blood loss weight of the group were significantly reduced. This is related to the direct blocking effect of the hydrogel on the wound. It can be seen from the figure that the commercial hydrogel, GMOSB S It stays on the wound surface, sealing the wound, slowing down blood outflow, and providing an environment for thrombosis. Compared with the commercial hydrogel group, GMOSB S The bleeding time and bleeding weight of the group were further reduced, which was due to the fact that the commercial hydrogel contained only a single hemostatic raw material (CS), while GMOSB S It contains not only GEL and SA derivatives that are beneficial to thrombus formation, but also TXA that inhibits thrombus degradation, ensuring that the thrombus quickly closes the wound from two directions.
[0118] After using the materials for 7 days, the AST, ALT and CRE levels in the rats' blood were detected to evaluate the effects of each hemostatic material on liver and kidney function. The results showed that the AST and CRE levels in the gauze group were significantly higher than those in the control group, indicating that liver and kidney function were damaged. Combined with the comparison of wound healing degree and bleeding volume, it was analyzed that this damage originated from the relatively slow wound healing speed in the gauze group, resulting in the degree of liver damage recovery lagging behind the other two groups in the same period of time. Commercial hydrogel group and GMOSB S There was no statistical difference in the various indicators of the group compared with the control group (healthy rats), indicating that commercial hydrogel, GMOSB S The use of this drug did not affect normal liver and kidney function ( Fig.15 ). To investigate GMOSB S Whether the use of GMOSB has an impact on other major organs, samples of the major organs of rats were taken after 7 days of treatment for pathological section analysis. S No pathological changes occurred in the main organs of the rats after the treatment. The results of liver and kidney function tests and the pathological analysis of the main organs confirmed that GMOSB S It has good metabolic safety in vivo. Fig.15 (A) is the serum alanine aminotransferase level; (B) is the serum aspartate aminotransferase level; (C) is the serum Cre level; (D) is the HE staining results of major organs.
[0119] 1.13. Evaluation of hemostatic properties in the femoral artery injury model of SD rats
[0120] After the mechanical strength and tissue adhesion strength of the material system were optimized, GMOSB S It can independently complete the hemostatic treatment of rat femoral artery injury, breaking the limitation of using cotton swab to press. Fig.16 GMOSB was observed in S It can cover the injured part of the femoral artery and quickly seal the wound. Compared with pressing with gauze, GMOSB S Significantly reduced bleeding time ( Fig.16 B). Good hemostatic performance is inseparable from ideal tissue adhesion and mechanical properties that can resist blood pressure shock. Gauze pressing is limited by volume and requires external force to press, so it cannot fit the wound well. Therefore, blood still slowly overflows from the wound in the early stage of hemostasis, and the wound cannot be completely closed. Continuous blood flow increases the difficulty of thrombus formation, thereby slowing down the hemostasis process. In contrast, thanks to its injectable properties, GMOSB S It can stably and accurately seal wounds and adhere precisely to the wound. Although blood will flow out slowly during the UV irradiation gelation period, the blood is effectively blocked with the formation of hydrogel and the secondary cross-linking of the spray. After a period of thrombosis, the excess GMOSB is gently removed. S It will not cause secondary bleeding. S Whether it will cause embolism, pain and motor dysfunction, the motor function of the affected limbs of rats was evaluated after 14 days of healing. Fig.16 As shown in C, there was no statistical difference in the muscle strength scores of the affected limbs of the two groups of rats 14 days after injury. Rats in both groups had slight movement restrictions, which was considered to be due to the fact that the wounds of the rats were not completely healed, there was still pain, and some skin overlap caused by sutures could not be fully stretched. The footprint areas of the affected limbs of the two groups of rats were counted using the gait analysis system ( Fig.16 D) Average footprint strength ( Fig.16 E) and standing time ( Fig.16 F). Statistical results showed that there was no significant difference between the two groups, indicating that GMOSB S No thromboembolism will occur, causing additional damage to the motor function of the rat's affected limb.
[0121] 1.14. Evaluation of hemostatic properties in the SD rat cardiac injury model
[0122] Heart bleeding has always been a difficult problem to stop bleeding. After the heart is damaged, the blood gushes out in a regular jet-like manner due to its own continuous contraction movement. In addition, the heart is the organ with the most concentrated blood in the whole body and plays a decisive role in maintaining the body's life. Therefore, patients with heart bleeding will lose a lot of blood in a short period of time and face the risk of death. To overcome this problem, try using GMOSB S Treat heart bleeding. Fig.17 As shown in the figure, a 10mL syringe needle is used to cause penetrating damage to the heart. After penetration, blood spurts out from the hollow structure of the needle and continues to gushed out rhythmically as the heart contracts. After confirming that the model is successful, GMOS is injected into the wound surface using a syringe and UV irradiation is performed at the same time. During the irradiation period, GMOS lost with the blood is replenished in time. When GMOS completely covers the wound, GMOS is cross-linked with a spray to ensure that GMOSB SThe wound can be completely sealed. After the hemostasis was completed, the chest cavity was temporarily closed. After 1 hour, the rat heart was observed and it was found that the rat heart maintained rhythmic beating and no secondary bleeding occurred at the wound. This proves that it is expected to be used in the hemostasis treatment of cardiac bleeding, which needs to be further verified by large animal experiments.
[0123] Example 2
[0124] In this example, multiple functional molecules are added based on the experimental batch 2 of Example 1:
[0125] 2.1. After the sodium alginate solution and the gelatin solution were mixed, 0.1% (w / w) of the antibacterial agent silver nitrate was added to the mixed solution, and then the mechanical strength and viscosity were tested.
[0126] 2.2. After the sodium alginate solution and the gelatin solution were mixed, 1% (w / w) of the coagulant fibrin was added to the mixed solution, and then the mechanical strength and viscosity were tested.
[0127] 2.3. After the sodium alginate solution and the gelatin solution were mixed, 1% (w / w) of the thickening agent transglutaminase was added to the mixed solution, and then the mechanical strength and viscosity were tested.
[0128] The above solutions can also achieve mechanical strength and anti-adhesion effects comparable to those of experimental batch 1.
[0129] Comparative Example 1
[0130] The anti-adhesion composite material was prepared by referring to the steps of experimental batch 1 in Example 1, except that the specific values of the parameters in steps 1.1 to 1.2 were different in different experimental batches, and the specific values are shown in Table 5:
[0131] Table 5. Specific parameter values for different experimental batches
[0132]
[0133] It can be seen from the above that the five parameters of the methacrylic acylated gelatin solution concentration, the oxidized sodium alginate solution concentration, the volume ratio of the gelatin solution to the sodium alginate solution, the calcium chloride aqueous solution concentration, and the volume ratio of the calcium chloride solution to the tannic acid solution in the preparation method provided in Example 1 of the present disclosure have a significant influence on the compressive strain and viscosity of the obtained cross-linked material, and there is an optimized range of values. The optimized range of values of the above five parameters provided in the present disclosure is proposed for the purpose of increasing the compressive strain while ensuring the viscosity, and is not a simple conventional choice.
[0134] Comparative Example 2
[0135] Multiple groups of anti-adhesion composite materials were prepared according to the steps of experimental batch 1 in Example 1, with the difference that in the first group, the solvent was replaced by water from phenyl-2,4,6-trimethylbenzoyl phosphinate lithium solution, the sodium alginate in the second group was unmodified, and the gelatin in the third group was unmodified, so as to obtain composite materials with different correlations, and then the viscosity and mechanical strength of the obtained composite materials were tested according to the test method in Example 1.
[0136] The test results of the three groups of experiments are shown in Table 6.
[0137] Table 6. Volume ratio of antimicrobial agent to gelatin aqueous solution in different experimental batches
[0138] Experimental Group Compression strain Average viscosity 1(3 groups in parallel) 71.2% 48.8kPa 2 (3 groups in parallel) 68.1% 30.2kPa 3 (3 groups in parallel) 66.9% 29.3kPa
[0139] As can be seen from Table 6, the choice of lithium phenyl-2,4,6-trimethylbenzoylphosphinate solution as a solvent helps to improve the compressive strain and has no significant effect on the viscosity. However, the unmodified sodium alginate and gelatin will reduce both the compressive strain and the average viscosity of the cross-linked material.
Claims
1. A combination of cross-linked materials, comprising a gel and a spray; the gel comprises two gel components, alginate and gelatin, at least one of the alginate and gelatin has undergone a modification reaction for the purpose of increasing the degree of cross-linking, or at least one of the alginate and gelatin contains a modification group that increases the degree of cross-linking; the spray contains one cross-linking component, two cross-linking components, or a combination of two or more cross-linking components that can undergo a cross-linking reaction with alginate and / or gelatin.
2. The cross-linked material combination according to claim 1, wherein: The alginate and gelatin in the gel are both modified, and self-crosslinking occurs between the two gel components and / or between the two gel components; preferably, the self-crosslinking is photo-crosslinking.
3. The cross-linked material combination according to claim 1, wherein: The alginate has a hydroxyl group, a carboxyl group, a phenol group, an aldehyde group or any combination thereof after an oxidative modification reaction; the gelatin contains a modification group, and the modification group is selected from an acetyl group or a part, a phenol group or a part, a thiol group or a part, a norbornene group or a part, a tetrazine group or a part, an azido group or a part, a furan group or a part, or any combination thereof; Preferably, the modifying group is methacryloyl and / or acryloyl.
4. The cross-linking material combination according to any one of claims 1 to 3, wherein: The mass ratio of alginate to gelatin is 1:(0.1-30), preferably 1:(0.5-30), and more preferably 1:(1-10); The spray contains a first cross-linking component and a second cross-linking component cross-linked with alginate and gelatin respectively, and the mass concentration ratio of the first cross-linking component to the second cross-linking component is (2-50):1, preferably (10-50):1, and more preferably (15-30):
1.
5. The cross-linked material combination according to claim 4, wherein: The molecular weight ratio of the first cross-linking component to the second cross-linking component is at least 1:(20-100).
6. The cross-linked material combination according to claim 4 or 5, wherein: The difference in monomolecular charge between the first cross-linking component and the second cross-linking component is at least 1; Preferably, the single molecule charge difference is 2.
7. The cross-linking material combination according to any one of claims 1 to 5, wherein: The cross-linking components include calcium ions and tannic acid.
8. The cross-linked material combination according to any one of claims 1 to 7, wherein the gel and / or spray further contains functional molecules, the functional molecules including but not limited to antibacterial agents, coagulants or viscosity enhancers; Preferably, the antimicrobial agent is selected from at least one of silver ions, antibiotics or antimicrobial peptides; Preferably, the coagulant is selected from at least one of tranexamic acid, carbon nanofibers, fibrin or thrombin.
9. The method for preparing the cross-linked material combination according to any one of claims 1 to 8, comprising a relatively independent method for preparing a gelling agent and a method for preparing a spraying agent; The preparation method of the gel comprises: after the alginate and gelatin are modified, aqueous solutions are prepared respectively, the concentration of the modified alginate in the modified alginate aqueous solution is 1% to 30% (w / v), the concentration of the modified gelatin in the modified gelatin aqueous solution is 5.0% to 30.0% (w / v), and then the two aqueous solutions are mixed in a volume ratio of 1:1 to 5:1; The preparation method of the spray comprises preparing aqueous solutions of different cross-linking components respectively and then mixing them evenly.
10. The preparation method according to claim 9, wherein: The modified alginate aqueous solution and / or the modified gelatin aqueous solution contains a photocrosslinking initiator; preferably, the photocrosslinking initiator is selected from one or more of phenyl-2,4,6-trimethylbenzoyl phosphinate lithium, benzophenone, 2-hydroxy-4'-(2-hydroxyethoxy)-2-methylpropiophenone, 2-hydroxy-2-methyl-1-phenylpropiophenone, 1-hydroxy-cyclohexylacetone, hydroxybenzophenone, benzoyldiphenylphosphine, benzophenone, and 2,2'-azobis(2-methylpropionitrile).
11. The preparation method according to claim 9 or 10, wherein: The cross-linking component includes calcium chloride and tannic acid. The preparation method of the spray includes: dissolving calcium chloride in water to prepare a 1.0% to 5% (w / v) calcium chloride solution, dissolving tannic acid in water to prepare a 0.1 g / ml solution, and mixing the calcium chloride solution and the tannic acid solution at a volume ratio of 1:1 to 1:
5.
12. The preparation method according to any one of claims 9 to 11, wherein: The preparation method of the gel and / or the preparation method of the spray further comprises the step of adding functional molecules.
13. Use of the cross-linked material combination described in any one of claims 1 to 8, or the cross-linked material combination prepared by the preparation method described in any one of claims 9 to 12 in the preparation of hemostatic, antibacterial or anti-adhesion products.
14. An implant dressing comprising the cross-linked material combination according to any one of claims 1 to 8, or the cross-linked material combination prepared by the preparation method according to any one of claims 9 to 12.
15. A portable tool box, comprising the cross-linked material combination according to any one of claims 1 to 8, or the cross-linked material combination prepared by the preparation method according to any one of claims 9 to 12.
16. A hemostatic device, comprising a pressure device, a dried implant material filled in the pressure device, and a spray, wherein the implant material comprises a gel in the cross-linked material combination according to any one of claims 1 to 8 or a gel in the cross-linked material combination prepared by the preparation method according to any one of claims 9 to 12; the spray comprises a spray in the cross-linked material combination according to any one of claims 1 to 8 or a spray in the cross-linked material combination prepared by the preparation method according to any one of claims 9 to 12; Preferably, the pressure applying device comprises a syringe.
17. A hemostatic platform or system comprising the hemostatic device of claim 16.